Polarization and Spectral Energy Distribution in OJ 287 during the 2016/17 Outbursts - Valtonen, Mauri; Zola, Stanislaw; Jermak, Helen; Ciprini, Stefano; Hudec, Rene; Dey, Lankeswar; Gopakumar, Achamveedu; Reichart, Daniel; Caton, Daniel; Gazeas, Kosmas; Matsumoto, Katsura; Ogloza, Waldemar; et al. (Galaxies, 2017)
We report optical photometric and polarimetric observations of the blazar OJ 287 gathered during 2016/17. The high level of activity, noticed after the General Relativity Centenary flare, is argued to be part of the follow-up flares that exhibited high levels of polarization and originated in the primary black hole jet. We propose that the follow-up flares were induced as a result of accretion disk perturbations, travelling from the site of impact towards the primary SMBH. The timings inferred from our observations allowed us to estimate the propagation speed of these perturbations. Additionally, we make predictions for the future brightness of OJ 287.